2020
DOI: 10.1080/23311975.2020.1720945
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in agro-processing and garment industry: Evidence from Ethiopia

Abstract: Currently, large industries like agro-processing and garment (Textile and Leather) industries in Ethiopia have interested to implement CSR activities. Hence, this study examined the causal relationship between stakeholders' and CSR implementation in agro-processing and garment industries based on employees' perceptions. After reviewing several works of literature we developed CSR implementation measurements. For analysis of CSR implementation, a total of 891 respondents were taken from agro-processing and garm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Some literature analyzes the influence of firm performance, firms' CSR practice, and CSR activities on firms' value using descriptive modes from the selected study area context. The causal relationship between stakeholders and CSR execution has been examined [23]. These findings reveal that the environment, customer, shareholder, and community significantly affect CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Some literature analyzes the influence of firm performance, firms' CSR practice, and CSR activities on firms' value using descriptive modes from the selected study area context. The causal relationship between stakeholders and CSR execution has been examined [23]. These findings reveal that the environment, customer, shareholder, and community significantly affect CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Of the survey-based CSR measurement tools, stakeholder-based operationalization based on "the six stakeholder group" has almost become a de facto in conceiving and measuring CSR practice (e.g., El Akremi et al, 2018;Fatma et al, 2014;González-Rodríguez et al, 2019;Jamali, 2008;Kumar et al, 2014;Mishra & Suar, 2010;Spiller, 2000;Turker, 2009;Valiente et al, 2012). A similar legacy is evident in the domestic literature (e.g., Asnake et al, 2019;Eyasu & Endale, 2020;Gemechu et al, 2020;Uvaneswaran et al, 2019). In a nutshell, the study employed a quantitative survey strategy.…”
Section: Methodsmentioning
confidence: 95%
“…As our systematic review indicated, almost all of the authors have quoted, impliedly or explicitly, the multistakeholder theory as their underlying theory. About one-fourth of the works have given a separate section in their literature review part to discuss the theory (Esubalew and Elifneh, 2018; Eyasu and Endale, 2020; Hailu and Nigatu, 2015).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Toward the first theme, a systematic literature review that focused on the academic inquiry of the practice of CSR in Ethiopia has been made. When the works are clustered state (regional state) wise to see where the works have been done, only a handful of papers resided in Amhara Regional State, Ethiopia: on manufacturing (Eyasu and Endale, 2020; Hailu and Rao, 2016), on hotels (Fentaw, 2016; Hailu and Nigatu, 2015), on Banks (Eshetu, 2019) and merchandise businesses (Uvaneswaran et al , 2019). The practice of CSR, however, is not different from the nationwide picture.…”
Section: Introductionmentioning
confidence: 99%